Effects of peroxisome proliferator activated receptor-α agonist on growth performance, blood profiles, gene expression related to liver fat metabolism in broilers fed diets containing corn naturally contaminated with mycotoxins - Zhang, Yong; Wang, Mengchen; Dong, Hao; Yang, Tan (Frontiers in Veterinary Science, 2023)
This study was conducted to determine the subclinical symptom of broilers exposure to mycotxoins from corn naturally contaminated, and the preventive effect with peroxisome proliferator activated receptor-α (PPARα) agonist (Wy-14643) supplementation. A total of 360 one-day -old male Arbor Acres broilers were randomly distributed into 4 treatments with 9 replicates of 10 birds. Dietary treatments included: Treatment 1, normal corn diets group; Treatment 2, normal corn + Wy-14643 diets group; Treatment 3, mycotoxin-contaminated corn diets group; Treatment 4, mycotoxin-contaminated corn + Wy-14643 diets. The supplementation of Wy-14643 was added at the expense of 0.01% and 0.02% corn in starter and grower diets, respectively. Birds fed mycotoxin diets had lower (P < 0.05) final body weight (BW), Body weight gain (BWG), feed intake (FI) and feed conversion ratio (FCR). Feeding mycotoxin diets reduced (P < 0.05) the levels of serum superoxide dismutase (SOD), glutathione peroxidase (GSH-PX), catalase (CAT), total antioxidative capacity (T-AOC) and high-density lipoprotein cholesterol (HDL-C), but higher malondialdehyde (MDA), triglyceride (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), aspartate aminotransferase (AST), alanine aminotransferase (ALT) and fatty acid synthetase (FAS). The supplementation of Wy-14643 increased (P < 0.05) the level of serum T-AOC, but reduced (P < 0.05) TG and LDL-C. Interactive effect was not observed (P > 0.05) in growth performance and blood profiles. The relative expression of PPARα mRNA and HMGCoA mRNA were increased (P < 0.05) in treatment 3 and treatment 4. The relative expression of ACO mRNA and APO-A were decreased (P < 0.05) in treatment 2 and treatment 3. The relative expression of CPT1 was higher (P < 0.05), while the mRNA relative expression of SREBP was lower (P < 0.05) in treatment 2, treatment 3 and treatment 4. The relative expression of ACO mRNA was increased (P < 0.05) in treatment 4. The mRNA relative expression of FATP4 was higher in treatment 2, but lower in treatment 3. Overall, feeding naturally contaminated mycotoxin diets caused negative effects on growth performance and blood profiles, while diet supplementation with Wy-14643 alleviate the detrimental effects on gene and protein expression related to liver fat metabolism in broilers.